P(3HB) Based Magnetic Nanocomposites: Smart Materials for Bone Tissue Engineering. (8th November 2016) - Akaraonye, Everest; Filip, Jan; Safarikova, Mirka; Salih, Vehid; Keshavarz, Tajalli; Knowles, Jonathan C.; Roy, Ipsita
Abstract : The objective of this work was to investigate the potential application of Poly(3-hydroxybutyrate)/magnetic nanoparticles, P(3HB)/MNP, and Poly(3-hydroxybutyrate)/ferrofluid (P(3HB)/FF) nanocomposites as a smart material for bone tissue repair. The composite films, produced using conventional solvent casting technique, exhibited a good uniform dispersion of magnetic nanoparticles and ferrofluid and their aggregates within the P(3HB) matrix. The result of the static test performed on the samples showed that there was a 277% and 327% increase in Young's modulus of the composite due to the incorporation of MNP and ferrofluid, respectively. The storage modulus of the P(3HB)MNP and P(3HB)/FF was found to have increased to 186% and 103%, respectively, when compared to neat P(3HB). The introduction of MNP and ferrofluid positively increased the crystallinity of the composite scaffolds which has been suggested to be useful in bone regeneration. The total amount of protein absorbed by the P(3HB)/MNP and P(3HB)/FF composite scaffolds also increased by 91% and 83%, respectively, with respect to neat P(3HB). Cell attachment and proliferation were found to be optimal on the P(HB)/MNP and P(3HB)/FF composites compared to the tissue culture plate (TCP) and neat P(3HB), indicating a highly compatible surface for the adhesion and proliferation of the MG-63 cells. Overall, this work confirmed the potential of using P(3HB)/MNP and P(3HB)/FF composite scaffolds in bone tissue engineering.